2008
DOI: 10.1002/adma.200702437
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Range Electron Transfer through a Single‐walled Carbon Nanotube Sheet

Abstract: A flow reactor system is designed for the reduction of cytochrome c mediated by a sheet of single‐walled carbon nanotubes, as schematically illustrated in the figure. The reaction kinetics of the reduction of cytochrome c by an added reductant solution is monitored by optical absorption spectroscopy to elucidate the mechanism of long‐range electron transfer in this novel bio‐inspired reactor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…After the cell was vacuum-pumped and refilled with N 2 gas three times, it was completely sealed and kept at 4 °C. The absorbances at 530 and 550 nm (Q-band) were used to calculate the concentration of each Cyt- c species ([Cyt- c ]) using a standard procedure. , The concentration of SWCNTs was low enough so that the absorption due to SWCNTs was negligible at these wavelengths.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the cell was vacuum-pumped and refilled with N 2 gas three times, it was completely sealed and kept at 4 °C. The absorbances at 530 and 550 nm (Q-band) were used to calculate the concentration of each Cyt- c species ([Cyt- c ]) using a standard procedure. , The concentration of SWCNTs was low enough so that the absorption due to SWCNTs was negligible at these wavelengths.…”
Section: Methodsmentioning
confidence: 99%
“…Reactivity of native SWCNTs in electron transfer reactions is known to depend on electronic structure and chirality. The SWCNT sample used in this study contains various chiral tubes. As a result, the electrochemical reduction potential of Cyt- c lies in the middle of those of native SWCNTs. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason of much slower back reaction in comparison with the forward one is the charge transportation in SWNT. 18,23,47 When an electron is injected into the SWNT it might travel away from the donor site until it gets trapped. Therefore, in order to neutralize the positively charged dye molecule, a trapped electron has to leave the trapping site and travel along SWNT again to the closest vicinity of the dye.…”
Section: Resultsmentioning
confidence: 99%
“…17 SWNT mediated long range electron transfer has been realized by incorporating both electron donators and acceptors onto the nanotubes. 23 By decorating individual semiconducting SWNTs with titanium dioxide (TiO 2 ) nanoparticles, 24 it has been shown that electrons are injected from TiO 2 nanoparticles to SWNT under UV irradiation and they return to TiO 2 when the UV light is cut off.…”
Section: Introductionmentioning
confidence: 99%